A semi-automatic planning technique for whole breast irradiation with tangential IMRT fields. (June 2022) - Marrazzo, L.; Redapi, L.; Zani, M.; Calusi, S.; Meattini, I.; Arilli, C.; Casati, M.; Compagnucci, A.; Talamonti, C.; Raspanti, D.; Pertutti, S.; Di Cataldo, V.; et al.
Highlights: A semi-automatic technique for whole breast RT with tangential IMRT fields was set. The technique was validated on a sample of 60 patients against manual clinical 3DCRT. AutoIMRT was shown to improve PTV coverage and homogeneity. No relevant differences in doses to OARs were observed. AutoIMRT plans were shown to be robust toward isocenter displacements. Abstract: Purpose: To implement a semi-automatic planning technique for whole breast irradiation with two tangential IMRT fields and to test the produced dose distribution against clinical 3DCRT plans, for introducing the technique in clinical practice. Methods: The Auto-Planning module of the Pinnacle 3 (Philips) treatment planning system was used for generating a Treatment Technique on left-sided breast cancer patients treated in free breathing or in deep inspiration breath hold (DIBH) and to right-sided breast cancer patients. The technique was evaluated against 3DCRT clinical plans in terms of dosimetric plan parameters. Plan robustness toward patient displacements was assessed on a subset of patients by inducing shifts to the isocenter. Results: A statistically significant improvement in target coverage and dose homogeneity was observed for autoIMRT. No statistically significant differences were observed for ipsilateral organs, except for the ipsilateral lung in left DIBH, where slightly lower Dmean and V18% are registered for autoIMRT. Slightly higher Dmean doses (although far below the constraints) to contralateral organs were observed for autoIMRT plans. AutoIMRT plans were shown to be as robust as 3DCRT plans toward isocenter shifts, with a maximum decrease in CTV coverage of −2.2% and −2.1% for autoIMRT and 3DCRT, respectively. Average planning times were 40 min for 3DCRT and 6 min for IMRT plans. Conclusions: The developed autoIMRT technique was proven to be advantageous for target coverage and homogeneity and sufficiently robust towards isocenter displacements. The use of automated planning consistently reduces the planning workload with improvements in plan quality.